Enhanced cadmium immobilization in soil using Fe- and Zn-doped biochar: Mechanisms and safety implications for Cicer arietinum L - Muzaffar, Uzma; Naveed, Muhammad; Naseem, Zainab; Abid, Iqra; Amir, Kashif Zulfiqar; Alamri, Saud; Siddique, Muhammad; Brtnicky, Martin; Mustafa, Adnan (Chemosphere, 2024)
Cd toxicity emerges as a major environmental concern with detrimental impacts on global agricultural systems and food safety. Therefore, there is an urgent need to cope with the high concentration of Cd in the soil and crops. This study elucidates the potential of iron (FeBC) and zinc doped biochar (ZnBC) on the growth and yield of chickpea (Cicer arietinum L.) in Cd-contaminated soil. The parallels of biochemical attributes and Cd absorption of Cicer arietinum L. were investigated after a 120-day pot trial under 1% (w/w) biochar doses and two Cd concentrations (25 and 50 mg kg-1). The results demonstrated that FeBC was more effective in promoting plant growth by reducing Cd mobility in soil than ZnBC and normal biochar (NBC). Additionally, the application of FeBC resulted in significant improvement in photosynthesis rate (53.98%), transpiration rate (91.53%), stomatal conductance (197%), and sub-stomatal conductance (213.33%) compared to other applied treatments. Cd uptake in roots, shoots, and grains was reduced by 44.19%, 56.89%, and 88.25% respectively with the application of FeBC. Notably, the highest decrease in Cd bioaccumulation factor (99.72% and 99.65%) and Cd translocation factor (99.89% and 99.85%) were recorded under FeBC application in 25 and 50 mg kg-1 Cd-contaminated soils, respectively. The improved plant growth and reduced Cd buildup with FeBC under Cd stress suggest that FeBC is a promising strategy to remediate Cd-contaminated soil and simultaneously promote sustainable production of legume crops in Cd-contaminated soils.
Keywords: Iron and zinc doped biochar; látky znečišťující půdu; Zinc; Environmental Restoration and Remediation; železo; Plant Roots; půda; fotosyntéza; kořeny rostlin; Soil Pollutants; Cadmium; Iron; Photosynthesis; Risk assessment; dřevěné a živočišné uhlí; Cicer; kadmium; zinek; Charcoal; regenerace a remediace životního prostředí; Bioremediation; Soil; Adsorption